Can Belgian firms cope with the Chinese dragon and the Asian tigers? The export performance of multi-product firms on foreign markets - Filip Abraham; Jan Van Hove (National Bank of Belgium, 2010)
Exporting firms are affected in many ways by competition on foreign markets. This paper focuses on the impact of Asian competition on the bilateral export performance of Belgian firms, controlling for firm level as well as destination-market characteristics. Export performance is measured in several ways, including the export intensity, the variety and quality of trade as well as the export intensity growth. Export performance appears to differ substantially across firms, across sectors and across destination markets. Our overall results indicate that both the export intensity and variety of Belgian firms' exports are reduced by Asian competition. Especially the competitive pressure caused by mainland China and Hong Kong is strong. The competitive pressure is intense in labour-intensive sectors but also felt in a wide range of activities with a higher value added. Belgian exporters cope with foreign competition by following a variety-expansion or a quality-upgrading strategy.
Keywords: F14; F15; L6; 330; multi-product firms; international trade; variety; quality; export intensity; competition; Asia; Exportwirtschaft; Mehrproduktfertigung; Internationaler Wettbewerb; Produktdifferenzierung; Produktqualität; Belgien